Land suitability assessment for apple (Malus domestica) in the Republic of Korea using integrated soil and climate information, MLCM, and AHP - Kim, Hojung; Shim, Kyomoon (International Journal of Agricultural and Biological Engineering, 2018)
Apples (Malus domestica) are one of the major fruits cultivated in South Korea and worldwide. To both sustain the productivity of apple trees and preserve the land, a land suitability assessment has been conducted. Two methods were used to analyze land suitability, a Most-Limiting Characteristic Method (MLCM) and an Analytic Hierarchy Process (AHP) with integrated soil and climate information based on the FAO classification framework. The most-limiting characteristic analysis showed that almost all areas were classified as marginally suitable (S3) or not suitable (N), which together accounted for 94.54% of the land in the Republic of Korea. On the contrary, AHP showed that S1 (34.1%) and S2 (44.17%) account for the majority of the land. Keywords: land suitability evaluation, biophysical modeling, GIS, land use planning, multi-criteria analysis, Republic of Korea DOI: 10.25165/j.ijabe.20181102.2522 Citation: Kim H, Shim K. Land suitability assessment for apple (Malus domestica) in the Republic of Korea using integrated soil and climate information, MLCM, and AHP. Int J Agric & Biol Eng, 2018; 11(2): 139–144.